Cultural Changes and Their Reflections on Social Organization - Analytical study - Dalia Tariq Abdel Fattah , Asst. Prof. Dr.; Firas Abbas Fadel, Lect Dr. (lark, 2024)
The subject of the research is about the beginning of culture and the implications of these developments at the social organizational level. Culture is the basis of social life, as it is a social phenomenon that no human group or society is devoid of. Cultural change is a human change. When culture adapts, it works to change the person who used it, and it is linked Change after that, as the world is experiencing radical and widespread changes that require attention and study because of their fundamental cognitive importance in all fields.Culture is the general framework that determines the intellectual content of the characteristics of society. Then it is the fruit of human activity, thought, and material production that man achieves. Accordingly, it represents the framework and pattern of relationships and interaction of individuals within society, and thus determines the social organization that results from this interaction, as culture makes individuals... Participation in society in a homogeneous, almost uniform way, since culture represents the nature of society and cultured techniques among the members of society, where the social organization of any group of individuals can be understood, through knowledge of the culture, and cultural change is reflected in the social organization, and the goal of the research is to identify what it is. Cultural diversity is changing and what are its implications for society and social organization in particularResearch is carried out in the analytical stage in explaining the problem of the study, and the research reaches a set of stages, the most important of which is:• Cultural change is an inevitable phenomenon in human societies thanks to the cognitive, scientific and technological openness we practice. .• Cultural change plays its role in social organization from multiple aspects, such as social organizational formation and organizational rotation• The beginning of the historical period witnessed by societies led to the creation of contemporary social organizations.• Human society is not static with changes because of the cultural secretions produced by modernity and scientific progress that are adhered to the members of society and contribute to changing their cultural history.
Keywords: culture, cultural basics, social organization.